Lessons in scientific computing : numerical mathematics, computer technology, and scientific discovery - Schorghofer, Norbert (CRC Press, Taylor & Francis Group, 2019)
"This new book is a modernized, exceptionally broad and intentionally compact introduction to scientific computing. It takes a broad and interdisciplinary approach; numerical methods, computer technology and their interconnections are treated with the goal of facilitating scientific research. Each chapter provides an insightful lesson, and viewpoints from several subject areas are often compounded within a single chapter. The material is written with an eye on usefulness, longevity, and breadth"--